Effect of the Dietary Inclusion of Full Fat Canola Seed on Performance of Quails - Eratak, Serdar; Cabuk, Metin (International Journal of Scientific Research and Management (IJSRM), 2019)
This experiment was conducted to study the effects of different levels of full fat canola seed low in glucosinolate and erucic acid on the performance of 336 day old quail (Coturnix coturnix japonica). The experiment was performed in a completely randomize design with three treatment and four replicates for each treatment. The experimental treatment included 5 and 10 % full fat canola seed in diet and fed to quail from 1 to 42 days of age. All of the experimental diets were iso-caloric and iso-nitrogenous. The mean total body weight was not significantly influenced by canola seed inclusion levels. But feed intake and feed conversion ratio were significantly increased by supplementation of 10 % full fat canola seed to the diet. Percentage of liver, proventriculus, gizzard, carcass to body weight was not significantly affected by canola seed inclusion levels. But small intestine rate was significantly increased by supplementation of 10 % full fat canola seed to the diet. As a result, it is possible to say that the full fat canola seed low in glicosinolate and erucic acid content could be used up to 10 % level in quails’ diet.